Soledad no Recife, K.: relato de uma busca e O irmão alemão: ditadura e trauma em três narrativas brasileiras - Soares, Maria Isolina de Castro (2019)
The research aims to study narrative works that approach in a literary way the period of Brazilian history between 1964 and 1985, during the military dictatorship. They are: Soledad no Recife (MOTA, 2009), K.: relato de uma busca (KUCINSKI, 2014) and O Irmão Alemão (BUARQUE, 2014). Traditional notions of history, literature, fictional fact and empirical fact are problematized, and the general objective is to construct a critical-theoretical document from the analysis of the selected material, in the light of the chosen theories. It is understood that the literature that brings, fictionalized, the testimony of traumatic events, transits in the "minefield" of reference and of self-reference, forming a "real" that constantly tries to escape. It also reveals itself as a possibility of revision of historical situations about which the official power has another version, and, in this sense, it can constitute an archive of authoritarian periods. The three works under analysis were chosen because they present anew the situations of terror lived during the dictatorship transformed into an aesthetic experience lived by characters who cease to be names forgotten by official history and begin to acquire the symbolic condition provided by the literary text to think about the “real". Thus, it is understood that literature is important for the comprehension of historical time, of the characteristics of the society in which the work was produced and that, either by giving literary existence to empirical facts narrated in first or third person in a testimonial perspective, or as autofiction, understanding the past can help build the future and can also help to reflect upon the threats that hover over the current political moment in different parts of the world, including Brazil, that crimes against humanity may reoccur.